PELATIHAN DASAR PUBLIC SPEAKING (PELATIHAN BAGI PEGAWAI NEGERI SIPIL DAN TOKOH MASYARAKAT DI WILAYAH DESA TAMAN BOGO KECAMATAN PURBOLINGGO, LAMPUNG TIMUR) - Wibawa, Agung; Sarwoko, Sarwoko; Sugiharto, Cahyono Eko; Suciska, Wulan (Prosiding Pengabdian FISIP Unila, 2012)
This public service activity aims to enhance the knowledge and to elevate the skill of related civilian servant officers. The activity also targets the society public figure, especially in the terms of public speaking,Â  in order to improve the quality of public service. In its broader scope, the research is hoped to provide positive support for those entities, particulary for their self development in reaching a better career opportunity.Â Â The activityâs subjects are civiliant servant officers and society public figure at Taman Bogo Village, Purbolinggo District, East Lampung Regency. This activity was held in form of speech, discussion and limited practice. It was followed by 24 people consist of 3 civiliant servant officers from surrounding villages and districts while the rest were the society public figures such as head of village, religious and youth leaders.Â Â The public service activity results show that there are considerable enhancement regarding the knowlegde of public speaking. This can be seen from the post test results as well as discussion during the activity. The same condition also applies for the participantsâ positive respond and motivation.Â Â Â Keywords: Public Speaking, Skill